Joseph Holloway's Abbey Theatre : a selection from his unpublished journal Impressions of a Dublin playgoer - Holloway, Joseph (Crosscurrents/modern critiques., 2009)
Until his death in 1944, Holloway attended almost every performance of the Abbey Theatre and daily recorded in his journal his reactions to plays and players and his comments about and conversations with literary and theatrical people. From the journal's 221 bulky volumes, housed in the National Library of Ireland, Mr. Hogan and Mr. O'Neill have compiled this book of extracts from the approximately 25,000,000 words written by the Irishman. The years from 1899 to 1926 were chosen because they are generally considered to be the significant ones for the Abbey Theatre: the year of.